The mediating effects of self-efficacy and study engagement on the relationship between specialty identity and career maturity of Chinese nursing students: a cross-sectional study - Yanjia Liu; Mei Chan Chong; Yanhong Han; Hui Wang; Lijuan Xiong (BMC, 2024)
Abstract Background Career maturity is a crucial indicator of career preparedness and unpreparedness can cause the turnover of new nurses. Considerable empirical work demonstrates the potential associations between specialty identity, self-efficacy, study engagement, and career maturity. This study aimed to explore the mediation role of self-efficacy and study engagement on the relationships between specialty identity and career maturity among Chinese nursing students. Methods Four hundred twenty-six Chinese nursing students were recruited between September 11 and October 30, 2022. The online survey was conducted following the CHERRIES checklist. Electronic questionnaires assessed their perceived specialty identity, self-efficacy, study engagement, and career maturity. The descriptive analysis, Harman single-factor analysis, Pearson correlation tests, structural equation modeling, and the bootstrap method were employed in data analysis. Results Bivariate correlation analysis identified a positive correlation between specialty identity, self-efficacy, study engagement, and career maturity (r = 0.276-0.440, P < 0.001). Self-efficacy and study engagement partially mediated the relationship between specialty identity and career maturity. Self-efficacy and study engagement played a chain mediating role between specialty identity and career maturity. Conclusions The underlying mechanism can explain the relationships between specialty identity and career maturity: a direct predictor and an indirect effect through self-efficacy and study engagement. Policymakers and educators should emphasize the importance of specialty identity and provide tailored strategies for improving care maturity depending on nursing students' specialty identity, self-efficacy, study engagement in the early stages of career development.